MOF (Metal Organic Framework) encapsulated polyoxometallate electro-catalytic material capable of being used for glycerol oxidation and preparation method of MOF encapsulated polyoxometallate electro-catalytic material

By in situ encapsulating polyoxygenate in metal organic frame materials, a heterogeneous catalyst for encapsulating polyoxygenate was prepared for MOF, which solved the problem of limited reserves and high price of glycerol oxidation electrocatalysts prepared by precious metal materials, and achieved efficient and stable glycerol oxidation catalysis.

CN119900052APending Publication Date: 2025-04-29UNIV OF SHANGHAI FOR SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411866741.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the prior art, glycerol oxidation electrocatalysts prepared by precious metal materials have limited reserves and high prices, which limit their practical application in electrolyzing aquatic hydrogen. Moreover, most metal organic frame electrocatalytic materials have poor conductivity and poor stability, which cannot meet the actual application needs.

Method used

By encapsulating the polyoxygenate in situ during the synthesis of metal organic frame materials, a heterogeneous catalyst for encapsulating the polyoxygenate was prepared, and the electrocatalytic material was synthesized on the foam nickel matrix by a one-step solvothermal reaction.

Benefits of technology

Efficient glycerol oxidation catalysis is achieved, with an industrial-grade current density required only a voltage of 1.35V, and good stability and catalytic performance are shown in continuous testing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119900052A_ABST
    Figure CN119900052A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new energy materials, and particularly relates to an MOF (Metal Organic Framework) encapsulated polyoxometallate electro-catalytic material capable of being used for glycerol oxidation and a preparation method of the MOF encapsulated polyoxometallate electro-catalytic material. And the electrocatalytic material is an MOF-74 material in which a Keggin type polyoxometallate H3PMo12O40 is encapsulated. The invention further discloses a preparation method of the metal-organic framework material. According to the invention, PMo12 molecules are introduced in a solvothermal reaction process, and a simple and convenient one-step method is adopted for in-situ synthesis of the MOF-74 (PMo12atMOF-74) electrocatalytic material with PMo12 encapsulated in pore channels on a foamed nickel matrix. The preparation technology provided by the invention is simple and convenient in process, the prepared electro-catalytic material can be directly used as a catalyst electrode, the electron interaction between a PMo12 object and MOF-74 promotes the generation of high-valence metal active species on the surface of MOF, and the obtained catalyst material has excellent GOR electro-catalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy materials, and in particular to an electrocatalytic material of a metal organic framework encapsulated polyoxometalate that can be used for glycerol oxidation and a preparation method thereof. Background Art

[0002] With the massive consumption of fossil fuels, energy shortages and environmental pollution have gradually become important issues restricting the sustainable development of human society, and thus clean renewable energy has attracted widespread attention. Among various emerging technologies, hydrogen production by water electrolysis is considered to be an important solution to meet human energy needs in the future. However, the oxygen evolution reaction (OER) in the water electrolysis process often requires a large overpotential due to its slow kinetics, and is prone to low energy conversion efficiency. In addition, there is a risk of explosion when the hydrogen precipitated from the cathode mixes with the oxygen produced at the anode. Therefore, replacing OER with an electro-oxidation reaction of organic molecules with a lower oxidation potential for hydrogen production by water electrolysis can not only reduce energy consumption and avoid risks, but also the oxidation of some organic molecules can produce high-value chemicals.

[0003] Glycerol oxidation (GOR) has recently been used as an alternative reaction to OER in water electrolysis for hydrogen production due to its low oxidation potential, abundant raw material sources, and high product added value. However, to date, the main GOR electrocatalysts are still precious metal materials, whose limited reserves and high prices greatly restrict the practical application of GOR in water electrolysis for hydrogen production. Therefore, the development of high-performance non-precious metal GOR electrocatalysts has become an important research direction in this field.

[0004] Metal organic framework (MOF) materials have attracted people's attention in the fields of catalysis, gas adsorption and energy storage due to their unique structural characteristics. However, due to poor conductivity and stability, the performance of most MOF electrocatalytic materials is still far from meeting the needs of practical applications. Encapsulating polyoxometalates (POM) in MOF nanocages is an important means to regulate the functionality of MOF materials. As reported in Reference 1 (A Keggin Polyoxometalate Shows Water Oxidation Activity at Neutral pH: POM@ZIF-8, an Efficient and Robust Electrocatalyst, Angewandte Chemie International Edition, 2018, 57: 1918), H6CoW is encapsulated in 12 O 40ZIF-8 shows good catalytic activity and stability when used for OER catalytic reactions in neutral media. Reference 2 (Oxygen Evolution Reaction Electrocatalytic Improvement in POM@ZIF Nanocomposites: A Bidirectional Synergistic Effect, ACS Applied Energy Materials, 2020, 3: 2925–2934) found that ZIF-67 encapsulating SiW9Co3 molecules exhibited good OER catalytic performance in alkaline media. However, the above work only studied the performance of related materials in conventional OER catalytic processes, without considering the GOR performance of the materials and the electro-oxidation performance of other organic molecules. In addition, the materials prepared in the above work are all in powder form, which need to be mixed with a binder and applied to the electrode surface when used, which not only easily blocks the active center, but also increases the internal resistance of the catalyst electrode.

[0005] In view of this, the development of highly active and stable self-supporting electrocatalytic materials based on MOFs is a key issue in realizing GOR to replace the anode OER reaction in the water electrolysis industry. Summary of the invention

[0006] The purpose of the present invention is to prepare an electrocatalytic material of MOF-encapsulated polyoxometalate that can be used for glycerol oxidation and a preparation method thereof through a simple and efficient process.

[0007] In order to achieve the above object, the present invention proposes the following technical solutions:

[0008] A metal organic framework encapsulated polyoxometalate electrocatalytic material for glycerol oxidation and a preparation method thereof, which realizes in situ encapsulation of POM molecules in MOF pores during MOF synthesis through a simple and efficient process, thereby preparing a POM@MOF heterogeneous catalyst and achieving efficient GOR catalysis.

[0009] The present invention proposes an electrocatalytic material of MOF-encapsulated polyoxometalates that can be used for glycerol oxidation. The electrocatalyst material comprises a metal organic framework material main material grown on a nickel foam substrate and polyoxometalate guest molecules encapsulated in pores of the metal organic framework material. The polyoxometalates are introduced during a solvent thermal reaction, and the electrocatalytic material of MOF-encapsulated polyoxometalates that can be used for glycerol oxidation is synthesized in situ on the nickel foam substrate using a one-step method.

[0010] The formation of this heterostructure, while retaining the porous structure of MOF, promotes the surface reconstruction of the catalyst and the generation of active metal centers during the reaction through the electronic interaction between the POM guest molecules and the MOF node metals, thereby obtaining excellent GOR catalytic activity.

[0011] Furthermore, the metal organic framework material is Co-MOF-74 or Ni-MOF-74.

[0012] Furthermore, the polyoxometalate is a Keggin-type polyoxometalate H3PMo 12 O 40 . Abbreviation for Keggin-type PMo 12 molecular.

[0013] Furthermore, the electrocatalytic material of the MOF-encapsulated polyoxometalate that can be used for glycerol oxidation has a rod-shaped microscopic morphology, and the diameter of the microrod is 5-8 microns.

[0014] Furthermore, the PMo 12 @MOF electrocatalytic material grows on the surface of nickel foam.

[0015] Furthermore, the PMo 12 @MOF electrocatalytic materials, PMo 12 The electronic interaction between the guest molecules and the MOF host promotes the generation of high-valent active species in the host material, so the catalyst has excellent GOR electrocatalytic performance.

[0016] The present invention also provides a method for preparing an electrocatalytic material of MOF-encapsulated polyoxometalate that can be used for glycerol oxidation, comprising the following steps:

[0017] Step 1: Prepare a Keggin-type polyoxometalate H3PMo using a solvent 12 O 40 , a mixture of 2,5-dihydroxyterephthalic acid, nitrate and a surfactant;

[0018] Step 2: Transfer the above mixed solution and the cleaned nickel foam substrate to a hydrothermal reactor for solvothermal growth at 120-125°C for 24-26 hours;

[0019] Step 3: After the reaction is completed, the mixture is washed three times with deionized water and ethanol and dried to obtain an electrocatalytic material of MOF-encapsulated polyoxometalate that can be used for glycerol oxidation.

[0020] Further, the nickel foam mesh is placed in a centrifuge tube, anhydrous ethanol is added to cover the nickel foam mesh, and after sealing, the nickel foam mesh is centrifuged and soaked in a centrifuge at 38-40° C. for 13-15 hours, and then taken out, and the soaked nickel foam mesh is placed in an overflow container, and 3.0-3.5 mol / L hydrochloric acid is continuously added from the bottom of the overflow container until the nickel foam mesh is covered and overflows, and after overflow cleaning for 15-20 minutes, the 3.0-3.5 mol / L hydrochloric acid is replaced with 2.0-2.5 mol / L hydrochloric acid, and after overflow cleaning for 15-20 minutes, 2 .0-2.5mol / L is replaced with 1.0-1.5mol / L hydrochloric acid, and after overflow cleaning for 10-15min, 1.0-1.5mol / L is replaced with deionized water and overflow cleaning is continued for 40-50min. Different concentrations of hydrochloric acid and deionized water are aerated by a micro-aerator to make the hydrochloric acid and deionized water full of bubbles during the overflow cleaning process, and the inside of the foam nickel mesh is cleaned by the bubbles. The cleaned foam nickel mesh is centrifuged and dehydrated in a centrifuge, and then dried in a drying oven at 53-55℃ for 5-6h to obtain a foam nickel substrate.

[0021] The present invention combines multi-stage pickling and deionized water cleaning, so that the surface and interior of the nickel foam mesh are cleaned more thoroughly, the pickling time is shortened, and the effect is better than that of single pickling. Cleaning with hydrochloric acid from high concentration to low concentration can more effectively remove oxides and impurities at different levels. High-concentration hydrochloric acid first dissolves the thicker oxide layer, while lower-concentration hydrochloric acid is used for fine cleaning to ensure that the nickel substrate is not excessively corroded, while the residual oxide is thoroughly removed; this deep cleaning not only improves the purity of the nickel foam mesh, but also enhances its bonding with the subsequently deposited MOF and POM materials, thereby improving the overall stability and catalytic efficiency of the electrocatalytic material. The clean substrate can better support the polyoxometalates encapsulated by the MOF, preventing the catalyst from falling off or deactivating under long-term use or high temperature conditions, which helps to extend the service life of the catalyst and maintain its long-term stable catalytic performance.

[0022] Furthermore, the solvent used to prepare the solution in step 1 is a mixture of DMF, anhydrous ethanol and water, and the volume ratio of the three is DMF:ethanol:water=(5-15):1:1.

[0023] Furthermore, Keggin-type polyoxometalate H3PMo 12 O 40 The feed concentration is 0.001-0.01mol / L.

[0024] Furthermore, the nitrate is cobalt nitrate or nickel nitrate.

[0025] Furthermore, the feed concentration of 2,5-dihydroxyterephthalic acid is 1.5-3 mg / mL.

[0026] Furthermore, the feeding concentration of cobalt nitrate or nickel nitrate is 6.6-13 mg / mL.

[0027] Furthermore, the surfactant includes sodium dodecylbenzene sulfonate, polyoxyethylene octylphenol ether (TritonX-100) and cocamidopropyl betaine in a mass ratio of 1:(1.3-1.5):(0.4-0.6).

[0028] Furthermore, the feed concentration of the surfactant is 0.4-0.5 mg / mL.

[0029] The present invention can improve the catalytic activity and stability of electrocatalytic materials by selecting surfactants of specific proportions. Under the conditions of the present invention, the surfactant can achieve an ideal mesoporous structure. By combining different types of surfactants, the micelle structure and the growth process of MOF can be optimized, thereby obtaining a more complex mesoporous morphology and guiding the formation of an ordered mesoporous structure. The surfactant molecules self-assemble into micelles or other ordered structures, which can serve as templates to guide the crystallization process of MOF and polyoxometalates, thereby forming a composite material with a specific morphology and pore size distribution; the surfactant can prevent aggregation between particles by adsorbing on the surface of nanoparticles, thereby controlling the particle size and morphology of the final product. This helps to obtain a uniformly dispersed, size-controlled nanostructure and improve the catalytic performance of the material.

[0030] Compared with the prior art, the advantages of the present invention are:

[0031] 1. The preparation process is simple, and PMo encapsulated on the nickel foam substrate can be prepared by only one step of solvent thermal reaction. 12 MOF-74 heterogeneous catalyst.

[0032] 2. PMo encapsulated in MOF pores 12 The electronic interaction between the guest molecules and the host material promotes the electron transfer from MOF to PMo 12 The transfer of metals is beneficial to the generation of high-valent metal (cobalt, nickel, etc.) active substances.

[0033] 3. Prepared PMo 12 @MOF electrocatalytic material has excellent GOR catalytic performance, and only 1.35V (vs.RHE) voltage is required to achieve industrial-grade (400mA / cm 2 ) and at a current density of 100 mA / cm 2 The performance did not decrease significantly after continuous testing for 120 hours (5 electrolysis cycles) at the current density.

[0034] 4. Prepared PMo 12@MOF electrocatalytic material can achieve a Faradaic efficiency of 94.89% for the production of formate at a voltage of 1.30 V (vs. RHE).

[0035] 5. PMo prepared by the present invention 12 @MOF electrocatalytic material is a self-supporting structure grown on a nickel foam substrate. It can be directly used in the electrocatalytic process without the use of binders and coating processes, which is conducive to exposing active sites and electron transfer between the catalyst and the current collector.

[0036] 6. The present invention combines multi-stage acid washing with deionized water washing to more thoroughly clean the surface and interior of the nickel foam mesh, thereby enhancing the bonding force between the nickel foam mesh and the subsequently deposited MOF and POM materials, thereby improving the overall stability and performance of the electrocatalytic material. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The PMo prepared in Example 1 12 @SEM photo of MOF;

[0038] Figure 2(a) is the PMo prepared in Example 1 12 @XRD pattern of MOF;

[0039] Figure 2(b) is the PMo prepared in Example 1 12 @FTIR spectrum of MOF;

[0040] FIG. 3 is a diagram of the PMo prepared in Example 1. 12 @Nitrogen adsorption / desorption curves and pore size distribution of MOF heterogeneous catalysts and MOF-74;

[0041] Figure 4 is the PMo prepared in Example 1 12 @Co2pXPS spectra of MOF and MOF-74;

[0042] Figure 5(a) is a diagram of the PMo prepared in Example 1 12 @LSV curves of GOR and OER reactions of MOF heterogeneous catalysts;

[0043] Figure 5(b) is the PMo prepared in Example 1 12 @GOR reaction LSV curves of MOF and MOF-74;

[0044] Figure 6(a) is a diagram of the PMo prepared in Example 1 12 @Faraday efficiency of MOF for producing formic acid at different voltages;

[0045] Figure 6(b) is a diagram of the PMo prepared in Example 1 12 @GOR stability curve of MOF. DETAILED DESCRIPTION

[0046] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be further described below.

[0047] The Keggin polyoxometalate H3PMo used in this example 12 O 40 , abbreviated as PMo 12 , purchased from Shanghai Titan Technology Co., Ltd.

[0048] Example 1

[0049] This embodiment 1 proposes a PMo 12 @MOF heterogeneous electrocatalytic material, the preparation method thereof is as follows:

[0050] Step 1: Under stirring conditions, 45 mg of 2,5-dihydroxyterephthalic acid, 200 mg of cobalt nitrate hexahydrate, and 45 mg of a surfactant are dissolved in a mixture of 30 mL of DMF, anhydrous ethanol, and water, wherein the volume ratio of DMF / anhydrous ethanol / water is 10:1:1. The surfactant includes sodium dodecylbenzene sulfonate, polyoxyethylene octylphenol ether (TritonX-100), and cocamidopropyl betaine (CAS: 61789-40-0) in a mass ratio of 1:1.4:0.5.

[0051] Step 2: Place the nickel foam mesh in a centrifuge tube, add anhydrous ethanol to cover the nickel foam mesh, seal it, centrifuge it at 39°C for 14 hours, then take it out, place the soaked nickel foam mesh in an overflow container, and continuously add 3.2mol / L hydrochloric acid from the bottom of the overflow container until it covers the nickel foam mesh and overflows. After overflow cleaning for 17 minutes, replace the 3.2mol / L hydrochloric acid with 2.3mol / L hydrochloric acid, continue to overflow and clean for 17 minutes, replace 2.3mol / L with 1.2mol / L hydrochloric acid, continue to overflow and clean for 13 minutes, replace 1.2mol / L with deionized water and continue to overflow and clean for 45 minutes. Different concentrations of hydrochloric acid and deionized water are aerated by a micro-aerator, so that the hydrochloric acid and deionized water are filled with bubbles during the overflow cleaning process, and the inside of the nickel foam mesh is cleaned by the bubbles. After the cleaned nickel foam mesh is centrifuged and dehydrated in a centrifuge, it is dried in a drying oven at 54°C for 5.5 hours to obtain a nickel foam substrate.

[0052] 0.03 mmol of PMo 12 Add to the above solution and stir evenly, then transfer together with the cleaned nickel foam (size 2cm×3cm) to a 50mL hydrothermal autoclave for solvothermal growth at 120°C for 24 hours.

[0053] Step 3: After the reaction, wash the sample three times with deionized water and ethanol, and then dry it to obtain PMo 12 @MOF catalyst sample.

[0054] The PMo prepared in Example 1 12 @SEM photos of MOF heterogeneous catalysts Figure 1 As shown in Figure 2, the MOF material grown on the surface of nickel foam presents a typical rod-shaped microstructure.

[0055] The PMo prepared in Example 1 12 The XRD pattern of @MOF heterogeneous catalyst is shown in Figure 2(a). As can be seen from the figure, MOF-74 material was successfully prepared on the surface of nickel foam by solvothermal method.

[0056] The PMo prepared in Example 1 12 The Fourier transform infrared spectrum (FTIR) of the @MOF heterogeneous catalyst is shown in Figure 2(b). In the FTIR spectrum of the heterogeneous structure, the appearance of Mo-O and Mo-O-Mo stretching vibration peaks indicates that PMo 12 The existence of molecules.

[0057] The PMo prepared in Example 1 12 The nitrogen adsorption / desorption curves and pore size distribution of @MOF heterogeneous catalyst and MOF-74 are shown in Figure 3. It can be seen that compared with the original MOF-74, PMo 12 The specific surface area and pore volume of the MOF samples were significantly reduced, indicating that part of the pores of the MOF-74 material were occupied by PMo 12 Molecular occupancy.

[0058] Figure 4 As shown, the PMo prepared in Example 1 12 @MOF heterogeneous catalyst and Co2pXPS spectrum of MOF-74. Compared with MOF-74, PMo 12 @MOF Co's characteristic peak shifts toward the high binding direction, indicating that PMo 12 The encapsulation of the guest molecules leads to the transfer of electrons from the MOF-74 host to the PMo 12 The transfer occurs, which is conducive to the generation of high-valent Co active species.

[0059] The PMo prepared in Example 1 12 @MOF heterogeneous catalyst was used as a self-supporting catalyst electrode, and the electrocatalytic performance was tested in 1M KOH and 1M KOH electrolyte solution containing 0.1M glycerol using a conventional three-electrode system. For comparison, the electrocatalytic performance of MOF-74 was tested under the same conditions. Figure 5(a) shows the electrocatalytic performance of PMo 12@MOF LSV curves of GOR and OER reactions. It can be seen that at 100mA / cm 2 At a current density of 1.5 , the potential required for the GOR reaction of this sample is 300 mV lower than that of OER, which fully demonstrates the potential and advantages of GOR in replacing OER. As can be seen from the GOR reaction LSV curve in Figure 5(b), PMo 12 The GOR performance of the @MOF catalyst is better than that of pure MOF-74; the sample only needs 1.12, 1.25 and 1.35 V (vs. RHE) to achieve 10, 100 and 400 mA / cm 2 The current density was 2.24 W, which showed excellent GOR catalytic activity.

[0060] Figure 6(a) is PMo 12 @MOF catalyst generates formate at different voltages. The Faradaic efficiency of formate generation at a voltage of 1.30 V (vs. RHE) is as high as 94.89%. Afterwards, the GOR stability of the catalyst was tested in constant current mode. Figure 6(b) shows the PMo 12 @MOF at 100mA / cm 2 GOR stability results at different current densities. During 120 hours of continuous operation, the voltage required for the GOR reaction increased slightly as the glycerol in the solution was gradually consumed; however, the GOR voltage recovered quickly after the electrolyte was renewed. The above results indicate that the sample has excellent GOR electrocatalytic stability.

[0061] Example 2

[0062] Step 1: Under stirring conditions, 90 mg of 2,5-dihydroxyterephthalic acid, 400 mg of cobalt nitrate hexahydrate, and 40 mg of surfactant are dissolved in a mixture of 30 mL of DMF, anhydrous ethanol, and water, wherein the volume ratio of DMF / anhydrous ethanol / water is 5:1:1. The surfactant includes sodium dodecylbenzene sulfonate, polyoxyethylene octylphenol ether (TritonX-100), and cocamidopropyl betaine in a mass ratio of 1:1.3:0.4.

[0063] Step 2: Place the nickel foam mesh in a centrifuge tube, add anhydrous ethanol to cover the nickel foam mesh, seal it, centrifuge it at 39°C for 14 hours, then take it out, place the soaked nickel foam mesh in an overflow container, and continuously add 3.2mol / L hydrochloric acid from the bottom of the overflow container until it covers the nickel foam mesh and overflows. After overflow cleaning for 17 minutes, replace the 3.2mol / L hydrochloric acid with 2.3mol / L hydrochloric acid, continue to overflow and clean for 17 minutes, replace 2.3mol / L with 1.2mol / L hydrochloric acid, continue to overflow and clean for 13 minutes, replace 1.2mol / L with deionized water and continue to overflow and clean for 45 minutes. Different concentrations of hydrochloric acid and deionized water are aerated by a micro-aerator, so that the hydrochloric acid and deionized water are filled with bubbles during the overflow cleaning process, and the inside of the nickel foam mesh is cleaned by the bubbles. After the cleaned nickel foam mesh is centrifuged and dehydrated in a centrifuge, it is dried in a drying oven at 54°C for 5.5 hours to obtain a nickel foam substrate.

[0064] 0.3 mmol of PMo 12 Add to the above solution and stir evenly, then transfer together with the cleaned nickel foam (size 2cm×3cm) to a 50mL hydrothermal autoclave for solvothermal growth at 120°C for 24 hours.

[0065] Step 3: After the reaction is completed, the sample is washed three times with deionized water and ethanol, and then dried to obtain PMo in Example 2. 12 @MOF catalyst sample.

[0066] The PMo prepared in Example 2 12 @MOF catalyst was electrocatalyzed and the results showed that the heterogeneous catalyst prepared under this condition had a high conductivity at 100 mA / cm 2 The voltage required for the GOR reaction was 1.31 V (vs. RHE) at a current density of , and the catalyst performance did not show obvious attenuation after 72 hours of continuous testing.

[0067] Example 3

[0068] Step 1: Under stirring conditions, 60 mg of 2,5-dihydroxyterephthalic acid, 26 mg of nickel nitrate hexahydrate, and 50 mg of a surfactant are dissolved in a mixture of 30 mL of DMF, anhydrous ethanol, and water, wherein the volume ratio of DMF / anhydrous ethanol / water is 15:1:1. The surfactant includes sodium dodecylbenzene sulfonate, polyoxyethylene octylphenol ether (TritonX-100), and cocamidopropyl betaine in a mass ratio of 1:1.5:0.6.

[0069] Step 2: Place the nickel foam mesh in a centrifuge tube, add anhydrous ethanol to cover the nickel foam mesh, seal it, centrifuge it at 39°C for 14 hours, then take it out, place the soaked nickel foam mesh in an overflow container, and continuously add 3.2mol / L hydrochloric acid from the bottom of the overflow container until it covers the nickel foam mesh and overflows. After overflow cleaning for 17 minutes, replace the 3.2mol / L hydrochloric acid with 2.3mol / L hydrochloric acid, continue to overflow and clean for 17 minutes, replace 2.3mol / L with 1.2mol / L hydrochloric acid, continue to overflow and clean for 13 minutes, replace 1.2mol / L with deionized water and continue to overflow and clean for 45 minutes. Different concentrations of hydrochloric acid and deionized water are aerated by a micro-aerator, so that the hydrochloric acid and deionized water are filled with bubbles during the overflow cleaning process, and the inside of the nickel foam mesh is cleaned by the bubbles. After the cleaned nickel foam mesh is centrifuged and dehydrated in a centrifuge, it is dried in a drying oven at 54°C for 5.5 hours to obtain a nickel foam substrate.

[0070] 0.15 mmol of PMo 12 Add to the above solution and stir evenly, then transfer together with the cleaned nickel foam (size 2cm×3cm) to a 50mL hydrothermal autoclave for solvothermal growth at 120°C for 24 hours.

[0071] Step 3: After the reaction is completed, the sample is washed three times with deionized water and ethanol, and then dried to obtain PMo in Example 3. 12 @MOF catalyst sample.

[0072] The PMo prepared in Example 3 12 @MOF catalyst was used for GOR electrocatalytic test. The results showed that the heterogeneous catalyst prepared under this condition had a high electrocatalytic activity at 100 mA / cm 2 The voltage required for the GOR reaction was 1.28 V (vs. RHE) at a current density of , and the catalyst performance did not show obvious attenuation after 48 hours of continuous testing.

[0073] Comparative Example 1

[0074] The difference between this comparative example and Example 1 is as follows: a foam nickel mesh is placed in a centrifuge tube, anhydrous ethanol is added to cover the foam nickel mesh, the foam nickel mesh is sealed, and the foam nickel mesh is taken out after being centrifuged and soaked at 42° C. for 10 hours in a centrifuge, and the soaked foam nickel mesh is placed in an overflow container, and 3 mol / L hydrochloric acid is continuously added from the bottom of the overflow container until the foam nickel mesh is covered and overflows, and after overflow cleaning for 90 minutes, 3 mol / L hydrochloric acid is replaced by deionized water and overflow cleaning is continued for 60 minutes, and hydrochloric acid and deionized water are aerated by a micro-aerator so that the hydrochloric acid and deionized water are filled with bubbles during the overflow cleaning process, and the inside of the foam nickel mesh is cleaned by the bubbles, and the cleaned foam nickel mesh is centrifuged and dehydrated in a centrifuge, and then dried in a drying oven at 50° C. for 7 hours to obtain a foam nickel substrate.

[0075] Comparative Example 2

[0076] The difference between this comparative example and Example 1 is that the surfactant includes sodium dodecylbenzene sulfonate, polyoxyethylene octylphenol ether (TritonX-100) and cocamidopropyl betaine in a mass ratio of 1:1:1.

[0077] Comparative Example 3

[0078] The difference between this comparative example and Example 1 is that the surfactant comprises sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium bromide and sodium lauryl sulfate in a mass ratio of 1:1.5:0.6.

[0079] Comparative Example 4

[0080] The difference between this comparative example and Example 1 is that no surfactant is added.

[0081] Performance Testing

[0082] The Faradaic efficiencies of the PMo12@MOF catalysts of Comparative Examples 1-4 for generating formate at different voltages were measured respectively. The results are shown in Table 1.

[0083] Table 1 Faraday efficiency performance test results of formate generation at different voltages

[0084]

[0085] As shown in Table 1, the Faraday efficiency of formate generated at a voltage of 1.30V (vs. RHE) is as high as 94.89%. In Comparative Example 1, the cleaning method of the nickel mesh substrate is changed, the ratio of the surfactant is changed in Comparative Examples 2-3, and no surfactant is added in Comparative Example 4. The Faraday efficiency of formate at different voltages decreases to varying degrees. At the same time, it is found through experiments that the catalyst performance of the electrocatalytic materials of Comparative Examples 1-4 is also attenuated to varying degrees after 48 hours of continuous testing, and the stability of the catalysts of Comparative Examples 1-4 is also reduced to varying degrees, indicating that the cleaning method of the nickel mesh foam and the type and ratio of the surfactant in the preparation method of the present invention have an important influence on the preparation of electrocatalytic materials with high activity and stability.

[0086] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any technician in the relevant technical field, without departing from the scope of the technical solution of the present invention, makes any form of equivalent replacement or modification to the technical solution and technical content disclosed in the present invention, which does not depart from the content of the technical solution of the present invention and still falls within the protection scope of the present invention.

Claims

1. A metal organic framework encapsulated polyoxometalate electrocatalytic material for glycerol oxidation, characterized in that: The electrocatalyst material includes a metal organic framework material main material grown on a nickel foam substrate and polyoxometalate guest molecules encapsulated in the pores of the metal organic framework material; by introducing polyoxometalates during a solvent thermal reaction, an MOF-encapsulated polyoxometalate electrocatalytic material that can be used for glycerol oxidation is synthesized in situ on a nickel foam substrate using a one-step method.

2. The electrocatalytic material of metal organic framework encapsulated polyoxometalate for glycerol oxidation according to claim 1, characterized in that: The metal organic framework material is Co-MOF-74 or Ni-MOF-74; the polyoxometalate is a Keggin type polyoxometalate H3PMo 12 O 40 . Abbreviation for Keggin-type PMo 12 molecular.

3. The electrocatalytic material of metal organic framework encapsulated polyoxometalate for glycerol oxidation according to claim 2, characterized in that: The metal organic framework material is Co-MOF-74 or Ni-MOF-74; the electrocatalytic material of the MOF encapsulated polyoxometalate that can be used for glycerol oxidation has a rod-shaped microscopic morphology, and the diameter of the microrod is 5-8 microns.

4. A method for preparing an electrocatalytic material of MOF-encapsulated polyoxometalate for glycerol oxidation according to any one of claims 1 to 3, characterized in that: The steps include: Step 1: Prepare a Keggin-type polyoxometalate H3PMo using a solvent 12 O 40 , a mixture of 2,5-dihydroxyterephthalic acid, nitrate and a surfactant; Step 2: Transfer the above mixed solution and the cleaned nickel foam substrate into a hydrothermal reactor for solvothermal growth at 120-125°C for 24-26 hours; Step 3: After the reaction is completed, the mixture is washed three times with deionized water and ethanol and dried to obtain an electrocatalytic material of MOF-encapsulated polyoxometalate that can be used for glycerol oxidation.

5. The method for preparing the electrocatalytic material of MOF-encapsulated polyoxometalate for glycerol oxidation according to claim 4, characterized in that: Place the nickel foam mesh in a centrifuge tube, add anhydrous ethanol to cover the nickel foam mesh, seal it, centrifuge it in a centrifuge at 38-40°C for 13-15h, then take it out, place the soaked nickel foam mesh in an overflow container, and continue to add 3.0-3.5mol / L hydrochloric acid from the bottom of the overflow container until it covers the nickel foam mesh and overflows. After overflow cleaning for 15-20min, replace the 3.0-3.5mol / L hydrochloric acid with 2.0-2.5mol / L hydrochloric acid, continue overflow cleaning for 15-20min, and replace the 2.0- 2.5mol / L is replaced by 1.0-1.5mol / L hydrochloric acid, and after overflow cleaning for 10-15min, 1.0-1.5mol / L is replaced by deionized water and overflow cleaning is continued for 40-50min. Different concentrations of hydrochloric acid and deionized water are aerated by a micro-aerator, so that the hydrochloric acid and deionized water are filled with bubbles during the overflow cleaning process, and the inside of the foam nickel mesh is cleaned by the bubbles. The cleaned foam nickel mesh is centrifuged and dehydrated in a centrifuge, and then dried in a drying oven at 53-55°C for 5-6h to obtain a foam nickel substrate.

6. The method for preparing the electrocatalytic material of MOF-encapsulated polyoxometalate for glycerol oxidation according to claim 4, characterized in that: The solvent used to prepare the solution in step 1 is a mixture of DMF, anhydrous ethanol and water, and the volume ratio of the three is DMF: ethanol: water = (5-15): 1:

1.

7. The method for preparing the electrocatalytic material of MOF-encapsulated polyoxometalate for glycerol oxidation according to claim 4, characterized in that: Keggin-type polyoxometallate H3PMo 12 O 40 The feed concentration is 0.001-0.01mol / L.

8. The method for preparing the electrocatalytic material of MOF-encapsulated polyoxometalate for glycerol oxidation according to claim 4, characterized in that: The nitrate is cobalt nitrate or nickel nitrate; the feeding concentration of cobalt nitrate or nickel nitrate is 6.6-13 mg / mL; the feeding concentration of 2,5-dihydroxyterephthalic acid is 1.5-3 mg / mL.

9. The method for preparing the electrocatalytic material of MOF-encapsulated polyoxometalate for glycerol oxidation according to claim 4, characterized in that: The surfactant comprises sodium dodecylbenzene sulfonate, polyoxyethylene octylphenol ether (TritonX-100) and cocamidopropyl betaine in a mass ratio of 1:(1.3-1.5):(0.4-0.6).

10. The method for preparing the electrocatalytic material of MOF-encapsulated polyoxometalate for glycerol oxidation according to claim 4, characterized in that: The feed concentration of the surfactant is 0.4-0.5 mg / mL.

Citation Information

Cited By

  • Transition metal-based heterojunction nano array electrode material and preparation method and application thereof

    CN122061183A